2008
DOI: 10.1007/s10811-008-9346-0
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution monitoring using the brown seaweed Padina durvillaei in the coastal zone of the Santa Rosalía mining region, Baja California Peninsula, Mexico

Abstract: The coastal marine sediments near Santa Rosalía on the eastern coast of the Baja California Peninsula (Mexico) are heavily polluted by metals due to copper mining and smelting over the past century (up to 1984). The present study compares the accumulation of metals in the brown seaweed Padina durvillaei from the central segment of the coast of Santa Rosalía (polluted by Co, Cu, Mn and Zn) and from two segments north and south of the known "hot spot". The seaweed samples were collected in May and August 2004 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
4
14
0
4
Order By: Relevance
“…Differences in concentration of cadmium between the two species could result from differences in metabolic rates or, more likely, to the affinity of each species for cadmium. Our results ( Table 2) were above the average values reported for macroalgae (0.92±1.32 mg kg −1 ) from five regions throughout the world (Baoli and Congquiang 2004 -Figueroa et al 2009), which is contaminated by waste from copper mining. However, this value is lower than in brown and red macroalgae along the coast of Chile that is also contaminated by waste from copper mining, where Andrade et al (2006) reports 17.8 mg kg −1 in Ahnfeltiopsis sp.…”
Section: Concentration Of Cadmiumsupporting
confidence: 44%
“…Differences in concentration of cadmium between the two species could result from differences in metabolic rates or, more likely, to the affinity of each species for cadmium. Our results ( Table 2) were above the average values reported for macroalgae (0.92±1.32 mg kg −1 ) from five regions throughout the world (Baoli and Congquiang 2004 -Figueroa et al 2009), which is contaminated by waste from copper mining. However, this value is lower than in brown and red macroalgae along the coast of Chile that is also contaminated by waste from copper mining, where Andrade et al (2006) reports 17.8 mg kg −1 in Ahnfeltiopsis sp.…”
Section: Concentration Of Cadmiumsupporting
confidence: 44%
“…Consequently, the third factor shown by factor analysis could be related to chemical processes associated with Mn reduction/dissolution. Similar relationships between Co and Mn were also found in coastal marine sediments and urban-rural topsoil (Rodriguez-Figueroa et al 2009;Chen et al 2008). Moreover, a significant correlation between Tl and Mn was found in French agrosystems (Tremel et al 1997), and Jacobson et al (2005) also found that Mn oxides may play a dominating role in Tl retention by soils.…”
Section: Discussionsupporting
confidence: 69%
“…were all within the ranges previously reported for these and other macroalgae in the Gulf of California and along the west coast of the Baja California Peninsula, Cd: 0.03-4.60 mg g 21 , Pb: 0.1-30 mg g 21 , Cu: 0.5-82 mg g 21 , Zn: 2-96 mg g 21 and Fe: 140-2898 mg g 21 )(Huerta-Díaz et al, 2007;Jara-Marini et al, 2009;Rodríguez-Figueroa et al, 2009;Riosmena- Rodríguez et al, 2010;Patrón-Prado et al, 2011).Cadmium levels in Codium simulans were similar to findings in C. amplivesiculatum Setchell & Gardner and C. cuneatum Setchell & Gardner at sites with no or little influence of human activity but subject to natural influences, such as upwelling(Huerta-Díaz et al, 2007). Moderate upwelling has been reported in Bahía de la Paz(Jiménez-Illescas et al, 1997).…”
supporting
confidence: 86%